PERAN LIVE STREAMING YOUTUBE REZA ARAP ‘MARAPTHON: THE LAST TALE’ DALAM MENINGKATKAN EXPOSURE DAN BRANDING PRODUK UMKM DI ERA DIGITAL - Andi Rinda Oktariani; Muh. Abudzar A. Galigo; Uswah Mujahidah Rasuna Said; Muhammad Yamin (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
The rapid development of digital platforms has created new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their marketing strategies through live streaming media. This study aims to analyze the role of Reza Arap’s YouTube live streaming entitled Marapthon: The Last Tale in enhancing MSME product exposure and branding in the digital era. A descriptive qualitative approach with a case study design was employed in this research. Data were collected through live streaming content observation, document analysis from online media sources, and literature review on digital marketing and influencer marketing. The findings reveal that Marapthon serves as an effective alternative promotional medium for MSMEs due to its massive audience reach, low promotional cost, and authentic real-time interaction between the creator and viewers. The effectiveness of promotion within this ecosystem is influenced by four main factors: large-scale audience reach, Parasocial relationships between the creator and audience, strong digital community engagement, and the authenticity of interaction during live streaming sessions. In addition to increasing product exposure, Marapthon also contributes significantly to building brand awareness and a positive brand image through organic endorsements by the content creator. This study highlights that entertainment-based live streaming is no longer merely a form of digital entertainment but has evolved into a participatory and interactive digital marketing ecosystem. It plays a significant role in strengthening MSME branding in the digital era. Therefore, live streaming based promotional models such as Marapthon can be considered a strategic alternative for MSMEs to enhance competitiveness in an increasingly competitive digital market.